(untitled) (Revista de Ciências Agroveterinárias, 2008)
The micropropagation has been used in order to multiply disease-free plants with desirable genetic traits. This technology has an important role to the Brazilian production of fruits, because the producers seek ways to produce fruit quickly and with high quality. This review has the objective to increase the knowledge of the in vitro rooting stage. The in vitro rooting is very difficult, especially for woody plants species. The response to rooting depends on endogenous and exogenous factors. The obstacles found in rooting are mainly caused by the interaction of these factors that makes difficult to isolate and characterize the variables involved in root formation. Each species or even cultivar of the same specie has different responses to in vitro rooting, due to specific genetic traits. Therefore, it is not possible to establish a general protocol of in vitro rooting for all species of the Rosaceae family.